2009
DOI: 10.1038/nm.2006
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of HIV-1 receptor–positive cells after HSV-2 reactivation is a potential mechanism for increased HIV-1 acquisition

Abstract: To explore the mechanism behind the association between HSV-2 and HIV-1 acquisition, we performed in situ analysis of the cellular infiltrate from sequential biopsies of HSV-2 lesions on and off antiviral therapy. CD4+ and CD8+ T cells, and a mixed population of plasmacytoid and myeloid dendritic cells (DCs), including cells expressing DC-SIGN, persisted at sites of HSV-2 reactivation for months after healing, even in the context of daily antiviral therapy. The CD4+ T cells that persisted reacted to HSV-2 anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
352
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(371 citation statements)
references
References 40 publications
17
352
1
1
Order By: Relevance
“…A recent study demonstrated that immune infiltrates persist well after the HSV-2 lesion has healed. The increased expression of DC-SIGN (DC-specific ICAM-3 grabbing non-integrin) on DCs in these infiltrates and T cell influx might contribute to HIV-1 susceptibility (10). Further studies are necessary to investigate the expression of langerin on LCs present in the healed HSV-2 lesions, because prolonged immune activation might lead to a decrease in the antiviral function of LCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated that immune infiltrates persist well after the HSV-2 lesion has healed. The increased expression of DC-SIGN (DC-specific ICAM-3 grabbing non-integrin) on DCs in these infiltrates and T cell influx might contribute to HIV-1 susceptibility (10). Further studies are necessary to investigate the expression of langerin on LCs present in the healed HSV-2 lesions, because prolonged immune activation might lead to a decrease in the antiviral function of LCs.…”
Section: Discussionmentioning
confidence: 99%
“…HSV-2 also induces inflammation, thereby including T cell influx, even in the absence of clinically apparent lesions. Furthermore, HIV-1-susceptible inflammatory cells can persist for a long period of time after HSV-2 infection has been cleared and the lesions have healed (10).…”
mentioning
confidence: 99%
“…Residual dermal DCs, plasmacytoid DCs (pDCs), and CD4 and CD8 T lymphocytes persist in the dermis between lesions. CD8 T lymphocytes are most superficial, with some present at the dermo-epidermal junction (8).…”
mentioning
confidence: 99%
“…For instance, the formation of pustules and ulcers by genital herpes may facilitate HIV-1 entry into mucosal tissues (10,11). Analyses of biopsies of HSV-2 lesions from patients revealed that HSV-2 reactivation resulted in an influx of activated CD4 + T cells, which may facilitate HIV-1 infection and subsequent dissemination (12,13). Immune activation of HIV-1 target cells, including dendritic cells and CD4 + T cells by HSV-2 infection, also likely enhances HIV-1 susceptibility (14).…”
mentioning
confidence: 99%